Etiological evaluation of congenital hypothyroidism in children over three years old in Chaharmahal and Bakhtiari province, Iran - Rostampour, Noushin; Hamidi, Majid; Taheri, Abdolmajid; Taslimi, Mina; Kheiri, Soleiman (Journal of Shahrekord University of Medical Sciences, 2025)
Background and aims: The etiology of congenital hypothyroidism (CH) is important in determining its severity, prognosis, genetic counseling, and clinical management. The present study was performed to investigate the etiology of CH in children in Chaharmahal and Bakhtiari. Methods: Screened children over the age of 3 years for hypothyroidism in the province were enrolled in this cross-sectional study. Then, in the case of permanent CH in the patient, demographic and laboratory findings, including thyroid-stimulating hormone (TSH) in primary screening, primary serum TSH, TSH after discontinuation of treatment, and age at the start of medication, were investigated, and patients were radiologically examined. The data were analyzed by SPSS 18 using descriptive statistics, a one-sample t-test, and a Chi-square test. Results: Dyshormonogenesis accounted for the most etiological percentage of the disease (72%), followed by dysgenesis (28%). Gender was significantly associated with etiology (P=0.022). Thus, dyshormonogenesis was more common in boys. The weight (P=0.564) and length at birth (P=0.978), maternal age (P=0.306), age at the beginning of medication (P=0.185), primary filter TSH (P=0.267), primary serum TSH (P=0.344), and TSH after discontinuation of medication (P=0.371) were not significantly associated with etiological factors. Conclusion: Among the etiological factors of CH, dyshormonogenesis was the most common cause among children in Chaharmahal and Bakhtiari province.